Environmental significance and geochemical speciation of trace elements in Lower Baram River sediments - Prabakaran, K.; Ramasamy, Nagarajan; Eswaramoorthi, S.; Anandkumar, A.; Francis, Merlin (Elsevier, 2019)
The geochemistry and distribution of major, trace and rare earth elements (REE's) was studied in the surface sediments of the Lower Baram River during two seasons: the Monsoon (MON) and Post – monsoon (POM). The major geochemical processes controlling the distribution and mobility of major, trace and REE's in the Lower Baram River surface sediments was revealed through factor analysis. The risk assessment of major and trace element levels was studied at three specific levels; i.e. the enrichment level [Contamination Factor (Cf), with the geo-accumulation index (Igeo)], the availability level [metals bound to different fractions, risk assessment code (RAC)], and the biological toxicity level [effect range low (ERL) and effect range medium (ERM)]. The results of all the indices indicate that Cu is the element of concern in the Lower Baram River sediments. The geochemical fractionation of major and trace elements were studied through sequential extraction and the results indicated a higher concentration of Mn in the exchangeable fraction. The element of concern, Cu, was found to be highly associated in the organic bound (F4) fraction during both seasons and a change in the redox, possibly due to storms or dredging activities may stimulate the release of Cu into the overlying waters of the Lower Baram River.